Edukasi Sertifikasi Halal UMKM Sektor Makanan dan Minuman Desa Panempan Pamekasan - Nur Ijabah; Zahrotul Fitriyah; Citra Nur Islamiyah; Amalia Rahmawatus Syafa’ah; Dian Dian; Farid Ardyansyah (Jurnal Masyarakat Mengabdi Nusantara, 2025)
Awareness of the importance of halal certification in Indonesia, especially among micro and small business actors (MSEs) in the food and beverage sector, is still low. This is in line with government regulations that require halal products for the Muslim majority community. The halal certification education program held in Panempam Village, Pamekasan, aims to improve the understanding and readiness of MSE actors in applying for halal certification according to the self-declare scheme regulated in the SEHATI program. This educational activity involved 20 MSE participants who attended discussion and training sessions to understand the concept of halal, the importance of certification, and application procedures in accordance with the latest regulations. Observations and interviews conducted in the initial stage showed a low understanding of MSE actors regarding halal certification procedures. However, after the education, there was an increase in knowledge and interest of participants to apply for halal certification. The results of this activity indicate that halal certification education can increase the awareness of MSE actors to produce safe, quality products that meet halal standards, which in turn will build consumer trust in local products. In conclusion, training like this plays an important role in encouraging MSEs to comply with regulations, increase product competitiveness in the market, and contribute to the regional economy. In the future, continued support in the form of technical assistance is expected to ensure the sustainability of the halal certification program among MSEs.